Significance of hyperferritinemia as a diagnostic and prognostic biomarker - M. I. Kaleda; E. S. Fedorov (Современная ревматология)
Ferritin is a complex protein composite (iron protein) that plays the role of the main intracellular iron depot in humans and animals, consisting of the protein apoferritin and the ferric atom in the composition of phosphate hydroxide. The reference value of ferritin in women is 200 μg/l, in men – 300 μg/l. Ferritin is a marker of total body iron stores, and low levels are specific for iron deficiency. Ferritin is also involved in immune processes and has both pro-inflammatory and immunosuppressive activity. Hyperferritinemia is a nonspecific symptom that occurs in a number of immunoinflammatory, infectious diseases, as well as during body iron stores overload. Hyperferritinemia is a criterion sign of macrophage activation syndrome in patients with systemic juvenile idiopathic arthritis, systemic lupus erythematosus and Kawasaki disease, as well as a predictive biomarker of adult-onset Still's disease. High ferritin levels occur in catastrophic antiphospholipid syndrome, as well as in infectious pathologies such as septic shock and COVID-19, including multisystem inflammatory syndrome associated with COVID-19. Ferritin concentration is an important parameter for assessing the activity and prognosis of the disease, which allows a rational approach to the choice of therapy in these patients.